Construction of an optical test-bed for eLISA. (May 2016) - Lieser, Maike; Fitzsimons, E; Isleif, K-S; Killow, C; Perreur-Lloyd, M; Robertson, D; Schuster, S; Tröbs, M; Veith, S; Ward, H; Heinzel, G; Danzmann, K
Abstract: In the planned eLISA mission a key part of the system is the optical bench that holds the interferometers for reading out the inter-spacecraft distance and the test mass position. We report on ongoing technology development for the eLISA optical system like the back-link between the optical benches and the science interferometer where the local beam is interfered with the received beam from the distant spacecraft. The focus will be on a setup to investigate the tilt-to-pathlength coupling in the science interferometer. To test the science interferometer in the lab a second bench providing a laser beam and a reference interferometer is needed. We present a setup with two ultra-stable low expansion glass benches and bonded optics. To suppress the tilt-to-pathlength coupling to the required level (few μm/rad) imaging optics are placed in front of the interferometer photo diodes.